2009
DOI: 10.1001/archdermatol.2009.94
|View full text |Cite
|
Sign up to set email alerts
|

Association of Psoriasis With Coronary Artery, Cerebrovascular, and Peripheral Vascular Diseases and Mortality

Abstract: To examine the cardiovascular risk factors in patients with psoriasis and the association between psoriasis and coronary artery, cerebrovascular, and peripheral vascular diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
306
0
9

Year Published

2011
2011
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 363 publications
(328 citation statements)
references
References 24 publications
13
306
0
9
Order By: Relevance
“…Prodanovich et al 79 2009 After controlling for risk factors, patients with psoriasis had a higher prevalence of ischemic heart disease, cerebrovascular, and peripheral vascular disease . Psoriasis was also found to be an independent risk factor for mortality 9 of 11…”
Section: Of 11mentioning
confidence: 99%
See 2 more Smart Citations
“…Prodanovich et al 79 2009 After controlling for risk factors, patients with psoriasis had a higher prevalence of ischemic heart disease, cerebrovascular, and peripheral vascular disease . Psoriasis was also found to be an independent risk factor for mortality 9 of 11…”
Section: Of 11mentioning
confidence: 99%
“…In a study of over 3,000 psoriasis patients from the Veteran's Administration Hospital database, investigators found higher prevalence rates of ischemic heart disease, stroke and PVD, after controlling for age, sex, DM, HTN, dyslipidemia, and smoking. 79 Recent high quality work revealed an increased risk of stroke for mild and severe psoriasis. 80 In particular, severe psoriasis confers an increased risk of stroke not explained by major risk factors alone.…”
Section: Peripheral Vascular Disease and Cerebrovascular Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…Most recently, a relationship between psoriasis and increased risk of myocardial infarction, cerebrovascular disease, and peripheral vascular (cardiovascular) disease has been reported (3)(4)(5). The observed excess risk appears to be greatest in younger patients and those with more severe psoriasis.…”
Section: Introductionmentioning
confidence: 99%
“…An increase in mortality is observed in patients with severe disease and is most pronounced in young patients. [3][4][5][6][7][8] Specific biomarkers aid in detecting disease, determining the activity and the severity and evaluating the response to therapy and monitoring disease progression. Cardiovascular biomarkers, many of which are also mediators of inflammation, have previously been studied in psoriasis patients.…”
Section: Introductionmentioning
confidence: 99%